Synchronizing developmental stages in Neotropical catfishes for application in germ cell transplantation - Arashiro, Dilberto Ribeiro [UNESP]; Yasui, George Shigueki [UNESP]; Calado, Leonardo Luiz; Nascimento, Nivaldo Ferreira do [UNESP]; Santos, Matheus Pereira dos [UNESP]; Alves do Santos, Silvio Carlos; Levy-Pereira, Nycolas; Monzani, Paulo Sergio; Siqueira-Silva, Diogenes Henrique; Senhorini, Jose Augusto [UNESP] (Cambridge Univ Press, 2018)
The aim of this study was to describe the effect of temperature on the fertilization, early developmental stages, and survival rate of two Neotropical catfishes Pimelodus maculatus and Pseudopimelodus mangurus. After fertilization, the eggs were incubated at 22 degrees C, 26 degrees C, and 30 degrees C, which resulted in fertilization rates of 96.95 +/- 1.79%, 98.74 +/- 0.76%, and 98.44 +/- 0.19% for P. maculatus and 96.10 +/- 1.58%, 98.00 +/- 0.63%, and 94.60 +/- 2.09% for P. mangurus, respectively. For P. maculatus, hatching occurred after 22 h 30 min post-fertilization at 22 degrees C, 16 h 30 min at 26 degrees C, and 11 h 20 min at 30 degrees C, and the hatching rates were 43.87 +/- 7,46%, 57.57 +/- 17.49%, and 53.63 +/- 16.27%, respectively. For P. mangurus, hatching occurred after 28 h 30 min post-fertilization at 22 degrees C and 17 h 30 min at 26 degrees C with respective hatching rates of 45.4 +/- 21.02% and 68.1 +/- 12.67%. For this species, all embryos incubated at 30 degrees C died before hatching. Additionally, for P. maculatus, the larvae from the lower (22 degrees C) and higher temperatures (30 degrees C) presented increased abnormality rates, as observed in the head, tail and yolk regions. The lowest abnormality rate was detected at 26 degrees C, which was considered the optimal incubation temperature for both species. The developed protocol enables the manipulation of embryonic development, which is important for the application of reproductive biotechniques, including chimerism and chromosome-set manipulation. The data obtained here are also important for the surrogate propagation of this species as P. mangurus was recently categorized as an endangered fish species.
Keywords: Incubation; PGC; Siluridae; Surrogate propagation; Temperature